Investigation of bolted RPC plate under direct tension - Prabha, S.Lavanya; Dattatreya, J. K.; Neelamegam, M.; Rao, M. V. Seshagiri (Journal of Structural Engineering, 2025)
Assembling of structural components like angle sections made up of conventional cementitious materials using bolted connections by drilling holes as in case timber structures is not feasible due to their limited tensile strength and low ductility. However, this could be possible in case of RPC due to the enhancements in these properties. The paper presents an investigation on the behavior of RPC bolted plates under direct tension. The effects of edge distance, fiber length and volume fraction on the performance of bolted elements were studied. The results show that a minimum edge distance of 3.5d, where d is the diameter of bolt hole and minimum fiber volume fraction of 2%-13mm fibers are more appropriate in terms of performance.